Социальная сфера: преобразование условий труда и быта - Андреев К. В. Константин Владимирович; Босенко Ю. Ф.; Вишневский А. Г.; Горюшин А. В.; Иванов В. Н. Валентин Николаевич (Москва, Наука, 1988)
Исключено из фонда НТБ ТПУ